Pengaruh Media Sosial dan Komunitas Online Terhadap Loyalitas Konsumen Produk Skintific: Peran Mediasi Keterlibatan Konsumen dan Hubungan Pengguna Merek - Safira, Jihan; Aryansyah, Ary (LPPM Institut Bisnis dan Informatika Kesatuan, 2023)
The empirical study explains that this research tests several variables such as the influence of social media platforms on brand consumer engagement, online-based brand communities on brand user relationships and the influence of brand consumer engagement and brand user relationships on consumer brand loyalty. The contribution of this research will enable practitioners and researchers social media platforms and brand communities obtain good information and encourage discussion regarding brand consumer involvement and user relationships with brands as moderating factors in consumer brand loyalty management. This research uses a quantitative method with snowball sampling, namely a questionnaire that tests several variables. Of the 216 questionnaires distributed to Skintific users in Indonesia, 196 cases were validly directed for analysis using SmartPLS 3. The results of the research explain that social media platforms have a positive effect on brand consumer engagement, online brand communities have a positive effect on brand user relationships, brand consumer engagement. Has a positive effect on consumer brand loyalty and brand user relationships also has a positive effect on consumer brand loyalty. We recommend future research directions regarding the cross-cultural impact of online brand communities on consumer purchasing decisions and corporate sales decisions. Although this research is a pilot study, it is important to note that it adds to the growing body of research in the field of social media marketing. Future research directions should focus on generalizing the scope of research by considering the scope of coverage of social media users worldwide.